Verification of the Forecasts for First Generation Biofuel Production in Poland in 2006-2008 - Szabela-Pasierbińska, Ewa (Weryfikacja prognoz produkcji biopaliw pierwszej generacji w Polsce w latach 2006-2008, 2010)
The article runs a verification of biofuels production forecasts in Poland in years 2006-2008, which have been provided with the use of one of the three models presented in the author's previous article. There has also been conducted a short analysis of events influencing biofuels market situation in Poland in years of the forecasts verification, the conclusions of which allow to claim that the most appropriate would be variant forecasts of bio-cthanol and biodiesel production output in Poland, which are the mixturp of quantitative and expert methods.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 145-150
Keywords: biofuels; quantitative and expert forecasting methods; formal models of the 2nd type; ex post errors